Two new species of the genus Trilacuna (Araneae: Oonopidae) from Jinyun Mountain of Chongqing, China - Huang, Ying; Bian, Dong-Ju; Tong, Yan-Feng; Zhang, Zhi-Sheng; Li, Shu-Qiang (European Journal of Taxonomy, 2021)
Two new species of the genus Trilacuna Tong & Li, 2007, T. jinyun Tong, Zhang & Li, sp. nov. (♂♀) and T. jiuchi Tong, Zhang & Li sp. nov. (♂♀), are described from Chongqing, China. Photos of the habitus and copulatory organs are provided.